Cuba: Three decades of innovation and development - Tran Xuan Hiep; Nguyen Anh Hung (International Journal of Cuban Studies)
The past three decades have been a period of great change in Cuba’s history. Cuba has remained steadfast in its socialist construction and renovation process, and thanks to the influence of favourable factors has overcome many difficulties and challenges on its own. This article studies the period of its development. It consists of three parts, after the Introduction and before the Conclusion. The first part provides an overview of Cuba’s renovation process over the past 30 years (1993–2023). The second part affirms, analyzes, and demonstrates typical factors that have directly impacted Cuba’s development and cooperation. The third part examines and evaluates Cuba’s development orientation and its prospects.